2011
DOI: 10.15835/nsb315595
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Plant Growth Regulators on Leaf Number, Leaf Area and Leaf Dry Matter in Grape

Abstract: Influence of phenylureas (CPPU) and brassinosteriod (BR) along with GA (gibberellic acid) were studied on seedless grape vegetative characteristics like leaf number, leaf area and leaf dry matter. Growth regulators were sprayed on the vines either once (7 days after fruit set or 15 days after fruit set) or twice (7+15 days after fruit set). CPPU 2 ppm+BR 0.4 ppm+GA 25 ppm produced maximum number of leaves (18.78) while as untreated vines produced least leaf number (16.22) per shoot. Maximum leaf area (129.70 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 4 publications
3
5
0
Order By: Relevance
“…It encourages the formation of shoots on growing vegetative growths on transplant and increasing the number of leaves by increasing the opening of lateral buds and the development of chloroplasts and chlorophyll biosynthesis through a course on the physiological processes responsible for those The increase in Photosynthesis, breathing and nutrient transfer from root to leaf increases the area of vegetative growths and delays their aging. This explains the increase in vegetative growth (Gundea , 2003, Zeng , 2016and Zhang , 2013 and These results are in agreement with those obtained by (Bhat , 2011 and Al-Karam , 2016) .…”
Section: Resultssupporting
confidence: 91%
“…It encourages the formation of shoots on growing vegetative growths on transplant and increasing the number of leaves by increasing the opening of lateral buds and the development of chloroplasts and chlorophyll biosynthesis through a course on the physiological processes responsible for those The increase in Photosynthesis, breathing and nutrient transfer from root to leaf increases the area of vegetative growths and delays their aging. This explains the increase in vegetative growth (Gundea , 2003, Zeng , 2016and Zhang , 2013 and These results are in agreement with those obtained by (Bhat , 2011 and Al-Karam , 2016) .…”
Section: Resultssupporting
confidence: 91%
“…The maximum peel weight (66.78 g) was observed from the treatment combination of GA 3 1000 ppm + Hand pollination which was on par with treatments GA 3 500 ppm + Hand pollination, GA 3 1500 ppm + Hand pollination, and GA 3 2000 ppm + Hand pollination (65.15, 64.38 and 61.97 g respectively). This is because more cell division by GA 3 , thereby increasing the cell density per unit volume (Bhat et al, 2012). The findings are in close conformity with earlier reports (Peng et al, 2004 andGomes et al, 2006).…”
Section: Peel Weight (G)supporting
confidence: 93%
“…The increase in peel weight in other treatment is may be due to more cell division by GA 3 , thereby increasing the cell density per unit volume (Bhat et al, 2012). The findings are in close conformity with earlier reports (Peng et al, 2004 andGomes et al, 2006).…”
Section: Peel Weight (G)supporting
confidence: 91%
“…The data related to seed content (%) are presented in the Bhat et al, (2012) in grapes. Paleg (1960 reported that exogenous application of growth regulators like GA 3 and other may induce amylolytic activity in isolated endosperm which resulted in the formation and release of reducing sugars.…”
Section: Seed Content (%)mentioning
confidence: 99%